The influence of curing time on mechanical properties and microstructure of taphole clay - Xiao Wang; Houyou Zhou; Wen-bo Zhao; Qingwen Li; Ya Yin (Scientific Reports)
Abstract As an important part of blast hole filling in blasting engineering, rapid setting taphole clay material has been paid attention by many scholars. Although curing time is an important factor affecting the mechanical properties of quick setting taphole clay materials, scholars have little research on quick setting taphole clay materials. This study investigated the influence of curing time on the mechanical properties of rapid-setting taphole clay materials, analyzed the variation pattern of mechanical strength during the increase of curing time, and employed techniques such as XRD and SEM-EDS to study the impact of curing time on the crystalline phase transformation, microstructure, and element distribution of taphole clay materials. The results revealed that with the increase of curing time, all mechanical strengths of the taphole clay materials increased significantly, with a faster growth rate within the first 6 h and stabilization around 24 h. The main hydration products of the taphole clay materials are calcium carbonate and ettringite, whose contents increase with curing time, promoting the hydration process and enhancing mechanical strength. The internal structure of the material becomes denser with increasing curing time, resulting in decreased porosity, specific surface area, the average pore size and total pore volume, and the formation of a dense spatial structure, which explains the trend of strength change. This study is of great significance for selecting optimal plugging materials and curing times for mines in China to achieve efficient blasting operations.